Os direitos fundamentais da personalidade como instrumento para atingir a dignidade da pessoa humana nas relações de trabalho - Sanvito, Paulo Celso (2011)
This paper addresses the fundamental rights, social and personality, and his performance in private relationships, with greater focus on employment, in order to verify the possibility of its impact on labor relations, overcoming a labor law purely economic and financial order the prevalence of human dignity, right through fundamental rights. Through a dialectical approach, analyzing by means of reasoning such as inductive, deductive and analogical fundamental rights, legal and historical aspects, this study seeks to demonstrate the resilience of the classical model of labor law, due to the changes that have occurred contemporary society due to globalization, against the imposition and effectiveness of fundamental rights to private, to enable its effectiveness in work relationships, including as a way to limit the directive power of the employer, demonstrating their fundamental rights, both individual and social, by workers